Stratification Economics: Core Constructs and Policy Implications - Chelwa, Grieve; Hamilton, Darrick; Stewart, James (Journal of Economic Literature, 2022)
This article introduces the core constructs of stratification economics to provide a coherent explanation for the persistence of intergroup inequalities. Aligned with the critical race theory concept of “the property rights in Whiteness,” stratification economics explicitly incorporates the concepts of identity-group investment and group-based agency in the construction of identity-group hierarchies. We survey the intellectual lineage, foundations, tenets and theoretical underpinnings of stratification economics, and conclude with a treatise on inclusive economic rights as an appropriate policy frame to empower people and counteract structural inequalities generated from inter-group conflict and competition for preferred outcomes. (JEL D63, G51, I14, I24, J15, J31, Z13)